PENGARUH VERBAL ENCOURAGEMENT TERHADAP SELF-EFFICACY MAHASISWA DALAM MENGERJAKAN KUIS BAHASA ISYARAT INDONESIA DASAR (BISINDO) - Purnama, Chandra Yudistira; Srisayekti, Wilis; Yanuvianti, Milda; Elsa, Katherine; Prastiwi, Anastasia A. P.; Clarissa, Clarissa; Loren, Listiarini W.; Metta, Deana (Jurnal Psikologi, 2024)
Self-efficacy is one of the essential things that students need to have, especially in academic performance. Self-efficacy has several sources, one of which is verbal persuasion in the form of verbal encouragement. Verbal encouragement can increase individual beliefs about their ability to complete tasks. This experimental study aims to determine the effect of verbal encouragement on self-efficacy.  The design used is a between-participant post-test only and conducted online. The sample of this study was 80 students of the Faculty of Psychology, Padjadjaran University, Bandung. The sample was randomly divided into two groups: The experimental group with verbal encouragement and the control group without intervention. Measurement of self-efficacy using two measuring instruments, General Self-efficacy Scale, which measures self-efficacy in general, and New General Self-efficacy Scale to measure self-efficacy more specifically, namely according to the research context. Data analysis using SPSS 26 and the results obtained based on the independent t-test showed that there was a significant effect of providing verbal encouragement on the level of self-efficacy of participants at p-value=0.0015 and p-value=0.000. This shows that giving verbal encouragement can increase the self-efficacy of participants who take tests, especially the Basic Indonesian Sign Language Quiz (BISINDO).